DETERMINING THE SKIN EFFECT BASED ON THE PRESSURE RECOVERY CURVE (American Journal of Technology and Applied Sciences, 2024)
This article presents some conclusions based on the results of studies in the well and the use of bottomhole conductivity, hydraulic conductivity and other properties of the reservoir to find the value of the skin effect, and at the same time taking into account the indicators of well No. 19 at the Shurchi field.